2015
DOI: 10.1021/acsnano.5b05252
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Ternary Bioinspired Nanocomposites via Synergistic Toughening of Reduced Graphene Oxide and Double-Walled Carbon Nanotubes

Abstract: With its synergistic toughening effect and hierarchical micro/nanoscale structure, natural nacre sets a "gold standard" for nacre-inspired materials with integrated high strength and toughness. We demonstrated strong and tough ternary bioinspired nanocomposites through synergistic toughening of reduced graphene oxide and double-walled carbon nanotube (DWNT) and covalent bonding. The tensile strength and toughness of this kind of ternary bioinspired nanocomposites reaches 374.1 ± 22.8 MPa and 9.2 ± 0.8 MJ/m(3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 39 publications
2
110
0
Order By: Relevance
“…C 1-3 ) Reproduced with permission. [88] Copyright 2015, American Chemical Society. D 1-3 ) Reproduced with permission.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…C 1-3 ) Reproduced with permission. [88] Copyright 2015, American Chemical Society. D 1-3 ) Reproduced with permission.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Gong et al [88] demonstrated a high-performance ternary bioinspired nanocomposite through a synergistic effect from 1D building blocks of double-walled carbon nanotubes (DWNTs) and covalent bonding of PCDO. The side view fracture morphology of the rGO-PCDO-DWNT nanocomposite film demonstrated the pull out of well-aligned DWNTs along the direction of tensile stress, as shown in Figure 7C 1 .…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Isogai and coworkers modified nanofibrillar cellulose with 2,2,6,6-tetramethylpiperidinyl-1-oxyl and composited it with saponite platelets to form a ternary artificial nacre, which showed a tensile strength of 420 MPa and strain-to-failure of 10%. [32] Other 1D nanofibers such as carbon nanotubes, [33,34] vanadium pentoxide (V 2 O 5 ) nanofibers, [29] and zirconium diboride [35] were also used to enhance the mechanical properties. Specifically, the ternary artificial nacre reinforced by V 2 O 5 nanofibers showed good shapememory performance, as well as excellent strength and toughness, owing to novel synergistic fashion 1D and 2D blocks.…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate the corrosion protection of various metallic substrates, versatile alternative practical coatings are being continuously developed such as conducting/ electroactive polymers, [10,11] conventional polymers containing filler with large aspect ratio [12,13] and polymer coatings with superhydrophobic surface [14,15]. Recently, great attention is paid to the potential of applications on bio-mimetic materials with super-hydrophobic surfaces structure due to their diverse potential and unprecedented hierarchical surfaces [16][17][18][19][20][21][22][23][24][25][26]. Moreover, the studies of anticorrosive polymer coatings with roughly superhydrophobic or biomimetic surface attracted intensive research interests [27][28][29][30][31][32][33][34].…”
mentioning
confidence: 99%